ACADEMIC STRESS AND COPING STRATEGY IN RELATION TO ACADEMIC ACHIEVEMENT - Abd Basith; Andi Syahputra; Slamat Fitriyadi; Rosmaiyadi Rosmaiyadi; Fitri Fitri; Susan Neni Triani (Jurnal Cakrawala Pendidikan, 2021)
Stress on students is more common and varied. Therefore, a good coping strategy is needed in order to control stress and increase academic achievement. The purposes of this study are: 1) to describe the level of academic stress and coping strategy; 2) to investigate the effect of the differences of gender, age, marital status, years of study and degrees on academic stress and coping; and 3) to analyze the relationship between academic stress, coping and academic achievement. This research used a quantitative method with a survey approach. The population was 340 Indonesian students in Wuhan, China. The samples of 184 students (73 male and 111 female) were taken with a simple random sampling technique. The instruments used in collecting data are the Scale for Assessment Academic Stress and the Stress Coping Style Inventory. The results showed that academic stress was at a moderate level dominated by cognitive stress indicators. Coping was at a moderate level dominated by active emotional coping. Different demographic factors have a significant effect on academic stress and coping. Intercorrelation shows the relationship between several indicators of academic stress and coping but no significant relationship with academic achievement.